Corporate indebtedness and macroeconomic stabilisation from a long-term perspective - Moritz Schularick (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Corporate debt levels have risen sharply in advanced and emerging economies before and during the Covid pandemic. Will corporate debt overhang slow down the recovery from the pandemic? This paper studies the aftermath of corporate debt surges in long-run cross country data. History shows that the macro-economic aftermath of corporate debt booms is typically benign. Three caveats apply, but none of them currently raises alarm bells: (i) the sectoral composition of corporate debt must not be tilted towards investments in the non-tradable sectors; (ii) legal institutions for debt reorganization must work efficiently; (iii) in bank-based financial systems, stringent banking supervision must prevent the emergence or survival of zombie companies.
Keywords: 330